1991
DOI: 10.1295/polymj.23.991
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Dichroism Study of Segmented Polyurethaneurea with Triblock Polyether Soft Segments

Abstract: ABSTRACT:Infrared (IR) dichroism study of segmented polyurethaneurea (SEUU) with ABA type triblock copolymer as a soft segment was carried out, where A stands for poly(oxyethylene) (PEO) and B stands for poly(oxytetramethylene) (PTMO). IR dichroism analysis of SEUU films under elongation suggested that the introduction of PEO units to the ends of PTMO brought about more aggregation of the hard segments, i.e., the better microphase separation in SEUU than segmented polyurethaneurea (SPUU) prepared from PTMO. Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The soft segments directly respond to stretching with a linear increase in the positive chain orientation as a function of strain, whereas hard-segment orientation function values remain zero before the onset of positive orientation at point E for PEO5-30. This behavior of hard segments was explained as the compensation of positively orienting small fibrillar hard segments by the negatively orienting lamellar hard-segment domains . There is slight positive orientation between E and F in fibrillar hard segments, and that continuous in soft segments marks the onset of a birefringence increase.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The soft segments directly respond to stretching with a linear increase in the positive chain orientation as a function of strain, whereas hard-segment orientation function values remain zero before the onset of positive orientation at point E for PEO5-30. This behavior of hard segments was explained as the compensation of positively orienting small fibrillar hard segments by the negatively orienting lamellar hard-segment domains . There is slight positive orientation between E and F in fibrillar hard segments, and that continuous in soft segments marks the onset of a birefringence increase.…”
Section: Resultsmentioning
confidence: 98%
“…Multicomponent thermoplastic polyurethanes consisting of alternating hard and soft segments offer unique mechanical properties that strongly depend on their backbone structure, composition, and resultant microphase morphologies. Even though these segments are semi-continuous, it was found that they exhibit distinctly different orientation responses to deformation. Rinke and Oertel conducted pioneering studies on the deformation behavior of stretched elastic polyurethanes using offline X-ray diffraction. Later, Cooper and Tobolsky used a torsional testing apparatus to find the origin of enhanced modulus on plasticizer-loaded polyurethane films .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The HS and SS are self-assembled at a nanometer scale due to microphase separation caused by the thermodynamic incompatibility between them. The microphase-separated structure depends on the HS content [ 6 , 7 , 8 , 9 , 10 ] and chemical structure [ 11 , 12 , 13 , 14 , 15 , 16 ], and can be changed by thermal annealing [ 17 , 18 , 19 , 20 , 21 , 22 ]. Since the HS domain acts as a physical cross-link point, the tensile property is correlated with the microphase-separated structure.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, they can consist of rigid units joined by flexible spacers that show thermotropic behavior on heating.' On the CCC 0021 -8W5/94/020207- 12 other hand, thermoplastic polyurethane elastomers are block copolymers of the ( A-B ) , type, consisting of alternating soft and hard segments. At service temperatures, the soft segment is in a viscous or rubbery state, whereas the hard segment is in a glassy or semicrystalline state.…”
Section: Introductionmentioning
confidence: 99%